Pengenalan Padi Toleran Pada Sawah Gambut Sapris Kenagarian Ketaping, Lembah Anai, Padang Pariaman - Haryoko, Widodo (Fakultas Pertanian Universitas Tamansiswa Padang, 2009)
The introduction of peat-tolerant rice varieties in peat soil was conducted in kenagarian Ketaping, Batang Anai sub-district, Padang Pariaman district from March to August 2009. The objective of this introduction is to transfer the knowledge and technology of planting peat-tolerant rice varieities in peat soil rice field areas. The introduction was conducted with extension and planting four high-yield rice varieties in demonstration plotting. The result of the introduction showed that four rice varieties Batang Piaman, Sunting Ameh, Sunting Bungo Durian and Randah Kuning could growth well and produce high yield on peat soil rice field